Prevalence and factors of overweight and obese among adolescent in Asia: a scoping review / Norihan Mat Hussin and Emmy Hainida Khairul Ikram - Mat Hussin, Norihan; Khairul Ikram, Emmy Hainida (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
This study aimed to estimate the prevalence or trends of overweight and obesity among adolescents in Asia countries and identify the associated risk factors between 2012 to 2020. The study design for this scoping review was carried out using SCOPUS, Web of Science and Google Scholar Databases for relevant studies in Asia countries. The inclusion criteria were Asian adolescents with ages ranging from 10 to 19 years old and geographical location. All studies on the prevalence and risk factors of overweight and obesity among adolescents in Asia countries were performed from September 2012 to the end of November 2020. Quality assessment and data extraction were based on The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Crosssectional studies. Overweight and obesity were higher among boys than girls although some reviews did not discuss which sex had a higher proportion of prevalence. In addition, there was some evidence about potential contributors to childhood overweight and obesity in Asia countries. Due to differences in survey sampling methods, sample size and age range of subjects, the prevalence and the risk factor of overweight and obesity required careful interpretation.